Implementing the Religious Moderation Curriculum in Islamic Schools for Gen-Z - Ana Zahratun Nisa; Mustapa Ahmad (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
Education in the era of globalization and digitalization presents Islamic schools with the significant challenge of developing a young generation that is not only academically competent but also moderate in religion. This article aims to analyze the implementation of a religious moderation curriculum in Islamic schools as an effort to foster tolerant, inclusive, and critical attitudes in the Gen Z generation. The research approach used a descriptive qualitative method, with literature review and limited interviews with teachers and students at Islamic schools in Indonesia. The results indicate that the integration of religious moderation values into the Islamic school curriculum occurs through several patterns: (1) adapting the syllabus and learning activities to the theme of tolerance and diversity, (2) using digital media and active reflection to capture the technology-oriented character of Gen Z, and (3) developing teachers as facilitators of value change. Obstacles identified include a lack of teacher training, limited learning media relevant to Gen Z, and the inherently conservative nature of school cultures. The conclusion of this study states that the implementation of a religious moderation curriculum in Islamic schools has significant potential to strengthen the moderate character of the Gen Z generation.